2022
DOI: 10.1016/j.jvacx.2022.100141
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) infection and vaccination: A cross-sectional study of college students’ knowledge, awareness, and attitudes in Villanova, PA

Abstract: Human papillomaviruses are major causative agents of multiple cancers including cervical, vulvar, penile, anal, and oropharyngeal cancers. Almost all sexually active individuals are exposed to HPV in their lifetime and although not all HPV genotypes are capable of causing cancers, several high-risk subtypes widely circulate. Several HPV vaccines have been developed and successfully utilized to limit the spread of these viruses and reduce rates of associated cancers. Despite their success, HPV vaccination rates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
14
0
2
Order By: Relevance
“…In view of the lack of a validated tool available for this study, a survey instrument was designed by the principal investigator (A.C.) of the study after conducting an extensive literature search on the impact of medical education on undergraduate students [ 3 , 4 , 7 13 , 15 ]. As part of the survey development process, a panel of experts in cancer survivorship (R.C., Y.K., C.J.T., Y.L.T., D.Q.N.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the lack of a validated tool available for this study, a survey instrument was designed by the principal investigator (A.C.) of the study after conducting an extensive literature search on the impact of medical education on undergraduate students [ 3 , 4 , 7 13 , 15 ]. As part of the survey development process, a panel of experts in cancer survivorship (R.C., Y.K., C.J.T., Y.L.T., D.Q.N.)…”
Section: Methodsmentioning
confidence: 99%
“…In view that cancer is more likely to affect older individuals, most young adults do not have extensive experience in interacting with cancer patients or managing complications associated with cancer. Within the United States, much of the cancer education within higher education is focused on prevention of skin cancer [ 2 , 3 ] or human papillomavirus [ 4 , 5 ]. Currently, didactic education on cancer is also primarily focused on healthcare students, with most educational program designed for medical [ 6 9 ] and nursing students [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The content of the measurement questions was developed based on previous studies. [25][26][27][28] The outcome measurement includes (1) knowledge about HPV and cervical cancer, (2) knowledge about the HPV vaccine, (3) attitudes toward HPV, cervical cancer, and HPV vaccine, (4) HPV vaccination practices, and (5) demographic characteristics, characteristics related to HPV, cervical cancer among students.…”
Section: Methodsmentioning
confidence: 99%
“…Although safe, efficacious vaccines against HPV have been available since 2006 for women and 2009 for men ( 6 , 7 ), many eligible young adults have chosen to delay or refuse HPV vaccination ( 8–10 ). Across all age-based populations in the U.S., college students have reported high rates of HPV prevalence along with low rates of HPV vaccination ( 11–13 ). The 2022 National College Health Assessment survey demonstrated that only 41% of male college students and 57% of female college students were up to date with recommended HPV vaccine series ( 14 ).…”
Section: Introductionmentioning
confidence: 99%